New approach of procurement market model for reactive power in deregulated electricity market - Singh A.; Kalra P.K.; Chauhan D.S. (My University, 2025)
In deregulated electricity market, reactive power management along with its pricing varies in different countries. In the paper, reactive power procurement model as two-level frame for the operation of a competitive market for reactive power services is discussed. In the first-level, i.e., reactive power procurement only with generators and condensers, may be taken up few months ahead with objective of minimization of reactive generation cost and real power loss, determined by ISO.In the second-level, reactive power dispatch,may be one and half hour ahead to real-time operation. Reactive power generation classification is argued to solve OPF.This framework may be adopted for any generic competitive electricity market. ©2009 IEEE.